ANALISIS MAKNA ASOSIATIF DALAM ALBUM TUTUR BATIN KARYA YUNITA RACHMAN - Nurhidayah, Ghina; Tarmini, Wini (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2023)
As the meanings continue to expand, there are various changes in meanings across different categories, one of which is associative meaning. Associative meaning refers to the meaning that a word carries, which is related to external circumstances beyond the language itself. The objective of this research is to identify the types of associative meanings in song lyrics, including (1) connotative meaning, (2) stylistic meaning, (3) affective meaning, (4) collocative meaning, and (5) reflective meaning. The research method employed is qualitative descriptive, and data collection techniques include observation and note-taking. The data used in this study consists of the lyrics from the album "Tutur Batin" by Yunita Rachman. The findings of this research reveal that associative meanings are present in 11 songs by Yunita Rachman. The identified types of associative meanings are as follows: connotative meaning related to values or metaphorical meanings, with a total of 23 instances; stylistic meaning associated with social differences, with 4 instances; affective meaning connected to the listeners' emotions, with 23 instances; collocative meaning, which is found in the same collocation.